Surgical treatment of stress urinary incontinence–trans‐obturator tape compared with tension‐free vaginal tape–5‐year follow up: an economic evaluation. (10th August 2016) - Lier, D; Robert, M; Tang, S; Ross, S
Abstract : Objective: To conduct an economic evaluation of the use of trans‐obturator tape (TOT) compared with tension‐free vaginal tape (TVT) in the surgical treatment of stress urinary incontinence in women. Design: Cost–utility and cost‐effectiveness analyses from a public‐payer perspective, conducted alongside a randomised clinical trial. Setting: Health services provided in Alberta, Canada. Sample: A total of 195 women participated in the randomised clinical trial, followed to 5 years postsurgery. Methods: Comparisons were undertaken between study groups for cost and two health‐outcome measures. Multiple imputation was used to estimate the 14% of missing data. Bootstrapping was used to account for sampling uncertainty. Sensitivity analyses were based on complete case analyses and the removal of a TVT patient with extreme health service cost. Main outcome measures: The 15D instrument was used to calculate quality‐adjusted life‐years (QALYs) for the primary analysis. Absence of serious adverse events was also analysed. Costs were based on inpatient and outpatient hospital use data and practitioner fee‐for‐service claims data. Results: The TOT group had a nonsignificant average saving of 2368 (95% CI −7166 to 2548) and incremental gain of 0.04 QALYs (95% CI −0.06 to 0.14) compared with TVT. TOT was dominant in over 71% of bootstrap replications and cost‐effective over a wide range of willingness‐to‐pay. Cost‐effectiveness analysis using the absence of an serious adverse events provided similar results. Conclusion: The results suggest that TOT is cost‐effective compared with TVT in the treatment of stress urinary incontinence. Tweetable abstract: The results of a 5‐year cost‐effectiveness analysis suggest that trans‐obturator tape is cost‐effective compared with tension‐free vaginal tape in the treatment of stress urinary incontinence. Tweetable abstract: The results of a 5‐year cost‐effectiveness analysis suggest that trans‐obturator tape is cost‐effective compared with tension‐free vaginal tape in the treatment of stress urinary incontinence.